China, India, And The Future of The World Economy : Fierce Competition Or Shared Growth? - Dimaranan, Betina (The World Bank, 2007)
Although both China and India are labor-abundant and dependant on manufactures, their export mixes are very different. Only one product-refined petroleum-appears in the top 25 products for both countries, and services exports are roughly twice as important for India as for China, which is much better integrated into global production networks. Even assuming India also begins to integrate into global production chains and expands exports of manufactures, there seems to be opportunity for rapid growth in both countries. Accelerated growth through efficiency improvements in China and India, especially in their high-tech industries, will intensify competition in global markets leading to contraction of the manufacturing sectors in many countries. Improvement in the range and quality of exports from China and India has the potential to create substantial welfare benefits for the world, and for China and India, and to act as a powerful offset to the terms-of-trade losses otherwise associated with rapid export growth. However, without efforts to keep up with China and India, some countries may see further erosion of their export shares and high-tech manufacturing sectors